2001
DOI: 10.1002/hup.327
|View full text |Cite
|
Sign up to set email alerts
|

The effects of caffeine on simulated driving, subjective alertness and sustained attention

Abstract: There is evidence that caffeine increases alertness and reduces fatigue. This may be especially so in low arousal situations (e.g. working at night or for prolonged hours). Caffeine has also been found to improve performance on vigilance tasks and simple tasks requiring sustained response. Again, these effects are often clearest when alertness is reduced, although there is evidence that benefits may still occur when the individual is unimpaired. Most studies to date have investigated the behavioural effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
87
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 33 publications
7
87
0
2
Order By: Relevance
“…The benefits of caffeine as a performance-enhancing substance have been extensively investigated, especially in endurance sports. The results of previous studies have shown that caffeine can cause increased alertness, focus and mental performance, decreased reaction time, increased time to fatigue, and increased endurance ability [2,6,13]. According to the report of the Committee on Military Nutrition Research and Food and Nutrition Board, United States Institute of Medicine in 2001 entitled "caffeine to maintain the mental performance in military operations", taking 150 mg of caffeine can increase endurance and physical performance among military forces [18].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of caffeine as a performance-enhancing substance have been extensively investigated, especially in endurance sports. The results of previous studies have shown that caffeine can cause increased alertness, focus and mental performance, decreased reaction time, increased time to fatigue, and increased endurance ability [2,6,13]. According to the report of the Committee on Military Nutrition Research and Food and Nutrition Board, United States Institute of Medicine in 2001 entitled "caffeine to maintain the mental performance in military operations", taking 150 mg of caffeine can increase endurance and physical performance among military forces [18].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine doses in the range of 3-6mg*kg -1 are considered to be optimum for ergogenic effects in both physical (5) and psychological (22,23,24) tasks whilst minimising any adverse side effects of caffeine ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of adenosine receptors by caffeine leads to increased alertness (Quinlan et al, 2000;Smit & Rogers, 2000;Smith, Sturgess, & Gallagher, 1999) and improvements to cognition, particularly reaction time (Durlach, Edmunds, Howard, & Tipper, 2002;Smit & Rogers, 2000) and vigilance (Brice & Smith, 2001;Childs & de Wit, 2006). It has been suggested that these effects merely represent alleviation of withdrawal in habitual caffeine consumers (James, 1994).…”
Section: Introductionmentioning
confidence: 99%